Doenças fúngicas em espécies florestais nativas na Amazônia Central - Assis, Luiz Alberto Guimarães de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Researches has shown that Forest plantations could accelerate the successive and ecologic processes of natural regeneration and degraded reas recovering, reestablishing the environment, conserving the soil and producing timber, thus contributing for deforestation reduction of native forests. Nevertheless, very little is known about the phytosanitary problems that happen in the species already established on those plantations. On this sense, it is aiming at to know the diseases that could affect the developing of plants, in 2005, it was conducted a pioneer survey at demostrative forest plantations areas in Manaus and Presidente Figueiredo - AM counties, where there were identified ten patogenous fungus causative of diferent spot – leaf and four fungus causative of soots found in the studied forest species: Cylindrocladium sp. and Meliola sp. in crab - wood (Carapa guianensis); Colletotrichum gloeosporioides, Sclerotium coffeicola and Meliola sp. in mahogany (Swietenia macrophylla); Cercospora sp., Rhizoctonia sp. Pseudobeltrania cedrelae and Meliola sp. in Cedar (Cedrela odorata); Cercospora bertholletia and Yamamotoa sp. in brazilian nut tree (Bertholletia excelsa); Erythrogloeum hymenaeae, Colletotrichum sp. Pestalotiopsis sp., Meliola sp., Asterina sp. and Amazonia sp. in stinking - toe (Hymenaea courbaril) and Rhizoctonia sp. in cork – wood (Ochroma piramidale). Tests of pathogenicity and reisolation of pathogenous were conducted at Inpa's green house and laboratories as well, following the Koch Postulate. In forest plantations, the illness severity found in a general approach was low quite. During the observing period, stinking - toe and cedar were the forest species that has shown the greatest illness incidence. It hasn't been found former registers about occurrences on Meliola sp. em mahogany, Cercospora sp., Rhizoctonia sp. e Meliola sp. in Cedar, Pestalotiopsis sp., Meliola sp., Amazonia sp. e Asterina sp. in stinking – toe and Rhizoctonia sp. in cork – wood. This is the very first register of these pathogenous attaching these species. x